Development of bionanocomposite reinforced with sugarcane bagasse nanocellulose and incorporated with natural antimicrobial agent for food packaging applications - Jimat, Dzun Noraini; Anuar, Hazleen; Sulaiman, Sarina; Samat, Noorasikin; Wan Salim, Wan Wardatul Amani; Asem Shehadeh Saleh Ali, Maimunah; Syed Putra, Sharifah Shahira (2018)
This study aims to develop the nanocomposite film with antimicrobial property towards alternative of current biodegradable plastics potential in food packaging. Polyvinyl alcohol (PVA) is chosen because it is the only synthetic polymer that is biodegradable and possess excellent film forming properties. This study used solution casting method to prepare the nanocomposite film of PVA/starch/nanocellulose. Nanocellulose was isolated from sugarcane bagasse by chemical pretreatment and ultrasonication methods and characterized by FESEM, AFM, XRD, and ATR-FTIR. The nanocellulose suspension were added into PVA/starch film with different loadings from 1 to 6wt% to determine the optimum loading that would give the best result of mechanical, thermal, and barrier properties. Antibacterial property of the film was prepared by incorporating essential oils into PVA/starch/nanocellulose film. Nanocellulose was successfully isolated from sugarcane bagasse as shown by their characterization analyses. The thermal properties, tensile strength, elongation at break and water vapour transmission rate (WVTR) of PVA/starch/nanocellulose showed improvement when the filler loading was 4wt%. Reinforcement of nanocellulose to PVA/starch significantly improved the tensile strength to 85 MPa. PVA/starch/nanocellulose film incorporated lemongrass essential oil showed the inhibition zone for S. aureus bacteria. This study is a small step towards development of active food packaging, by incorporating nanocomposite biodegradable film with natural antimicrobial agent.